CARD14 Missense Variant Underlying CARD14-Associated Papulosquamous Eruption with Beneficial Response to Secukinumab - Shangzhi Dai; Shanshan Zhang; Chenliang Wang; Xin Lin; Zhimiao Lin (Elsevier, 2023)
CARD14-associated papulosquamous eruption is an autosomal dominant genodermatosis characterized by early-onset, generalized erythematous patches and plaques with prominent scales, mostly with facial involvement. Heterozygous gain-of-function variants in the CARD14 gene have been reported to be causative for this entity. The pathogenesis mainly involves the IL-23‒IL-17 inflammatory circuit, yet the efficacy of anti‒IL-17 treatment remained less examined. In this study, we report one previously unidentified variant underlying the CARD14-associated papulosquamous eruption and showed its gain-of-function property. Furthermore, we present the beneficial effect of anti‒IL-17A treatment in our patient.